EFFECTS OF AIRPORT SERVICE QUALITY ON AIRLINE PASSENGER SATISFACTION: A CASE OF JULIUS NYERERE INTERNATIONAL AIRPORT, TANZANIA - Mapunda, Hussein M.; Mwageni, Denis (Journal of Industrial Engineering & Management Research, 2025)
This study examines how the Dimensions of airport service quality, such as airport facilities, the airport environment, and security screening practices, affect passenger satisfaction at Julius Nyerere International Airport (JNIA) in Tanzania.It addresses a critical gap in understanding service perceptions within African international airports. A quantitative design was used, employing structured questionnaires for data collection. International departure passengers were surveyed using convenience sampling. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4 software. The model evaluated the strength and significance of relationships among constructs. Results showed that security screening practices had the strongest positive effect on satisfaction. The airport environment had a moderate influence, whereas the airport facilities had the least impact. All three dimensions were statistically significant. Findings highlight the role of procedural efficiency and physical infrastructure in shaping passenger experiences. SSP indicators such as staff professionalism and responsiveness were key contributors. The study recommends prioritizing improvements in security transparency and staff training. It also suggests investing in spatial design and environmental quality. Policymakers should revise service frameworks to reflect these dimensions. Future research should expand to other airports for broader applicability.